Optimization of a Comprehensive Prehabilitation Program for Patients with Stable Coronary Artery Disease Undergoing Elective Coronary Artery Bypass Grafting - Yu. A. Argunova; T. N. Zvereva; S. A. Pomeshkina; A. V. Ivanova; O. M. Polikutina; O. V. Gruzdeva; V. V. Kashtalap; O. L. Barbarash (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the effectiveness of a comprehensive prehabilitation program including the optimization of drug therapy for patients undergoing elective coronary artery bypass grafting (CABG).Material and methods. 56 male patients with stable angina referred to elective on-pump CABG were enrolled in a study. All patients were screened for eligibility according to the inclusion/exclusion criteria and then randomized into two groups. Group 1 patients (n=28) underwent preoperative management (prehabilitation) for 14 days, including patient education and physical rehabilitation. Trimetazidine in a dose of 80 mg per day was added to the standard drug therapy. Group 2 patients (n=28) underwent similar preoperative management, but with the standard drug therapy without trimetazidine. In addition to the routine methods of preoperative management, all patients underwent the 6-minute walk test (6MWT) to assess exercise tolerance and speckle tracking echocardiography to measure left ventricular (LV) longitudinal deformation. Serum troponin T was measured in all patients. The measurements were performed at admission and after the surgery.Results. Patients did not differ in the main clinical and demographic data, as well as the main preoperative speckle tracking echocardiography findings. The intraoperative parameters were comparable in both groups. The rate of early postoperative complications was 61% (n=17) in Group 1 and 64% (n=18) in Group 2 (p>0.05). LV ejection fraction significantly decreased postoperatively in both groups (p<0.01) as well as LV longitudinal deformation as compared to the baseline. Patients receiving the standard therapy without trimetazidine reported a significant decrease in the longitudinal strain after CABG compared with the baseline (p=0.01). There were no statistically significant differences in most preoperative and postoperative indicators of longitudinal deformation among patients treated with trimetazidine. Postoperative values of GLPS-LAX and GLPS-Avg were significantly higher in the trimetazidine group than those in the control group (p=0.04). Group 1 patients reported longer distance covered in 6MWT than Group 2 patients while assessing exercise tolerance: 370.0 [260.0;415.0] vs 242.0 [202.0;350.0] m, respectively (p=0.0059).Conclusion. The addition of trimetazidine in a dose of 80 mg daily in the prehabilitation program for patients undergoing elective CABG demonstrated better postoperative indicators of LV longitudinal deformation and an increase in exercise tolerance. Obtained findings allowed considering this approach to the preoperative management as an additional method of cardiac protection and optimization of the functional status of patients.